RESEARCH OF SOCIAL, DEMOGRAPHIC, MATERIAL AND CULTURAL ASPECTS OF LIFE OF PUBLIC UNIVERSITY STUDENTS IN THE REPUBLIC OF SRPSKA - Trninic, Dusko (Politeia, 2023)
This paper presents socio-demographic, socio-economic, and socio-cultural aspects of a research into living conditions of public university students in the Republic of Srpska, with a view to designing their social and sociological profile. The research was conducted during the 2020/2021 academic year at both public universities of the Republic of Srpska, with the respondents coming from different faculties and scientific/scholarly fields. The results gained reveal that the majority of students do not leave parental homes during their academic studies and that it is their parents who financially support them and provide for their tuition fees. On average, the parents belong to middle-classes, with their monthly income not exceeding, in most cases, the amount of average salary in the Republic of Srpska for the period designated or, rarely, the amount of two or two and a half average salaries. The students follow the traditional living model and they are mostly religious, where the dominant denomination is that of the Serbian Orthodox Christian Church. There is a pronounced significance of the traditional family setting and patriarchal patterns of behaviour, given that the respondents maintain that they choose to discuss important life issues and private situations within their primary families and with their close relatives. The importance of family and family values is further accentuated in the respondents by the proclaimed life goals, since most of them claim that establishing and maintaning close (partner) relationships is on the top of priority list in their lives. With regard to the aforementioned, one can draw a conclusion that public university students in the Republic of Srpska are dependent upon both their families and their wider social community, with (post)modern processes of liberalisation, detraditionalisation, and individualisation having no significant impact on their collective and individual lives.